Relationship of Cystein Rich Protein Gene Polymorphism with Sheep Immunity - Al-Omairi, Majeed Sh. S.; Nasan, Sabah Mohammad Al-Haj (American Journal of Biology and Natural Sciences, 2025)
The study was conducted at the Private Station on samples consisting of 60 blood samples taken from 60 Awassi ewes during their 3rd lambing season in the year 2023. The system used for sheep breeding at the station is in open and semi-open pens, with closed facilities for young lambs. Results showed a significant effect of SNP in exone 2 from CSRP-1 gene on all immunity parameters (P<0.05), TNF-α altered significantly and the highest concentration was recorded in sheep with wild genotype (74.99 pg/ml) compared with the sheep with mutant genotype (60.14 pg/ml). IgA, TGF-β and IL-6 differed significantly (P<0.05) between wild and mutant groups, the highest concentration were recorded in wild group namely, 201.07µ / ml, 60.84 pg/ml and 494.55 pg/ml respectively. The TNF-α altered significantly and the highest concentration was recorded in sheep with wild genotype (70.90 pg/ml) compared with the sheep with mutant genotype (64.24 pg/ml). IgA and IL-6 differed significantly between wild and mutant groups and the highest values were noticed in wild namely, 220.07 and 290.05 pg / ml respectively compared with values in mutant group namely, 161.02 and 393.79 pg / ml respectively. Results showed that the IL-1β and TGF-β did not differed significantly between wild or mutant groups according exon 5 position.